2010
DOI: 10.1210/endo.152.2.zee742
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Room Light before Bedtime Suppresses Melatonin Onset and Shortens Melatonin Duration in Humans

Abstract: This article appears in The Journal of Clinical Endocrinology & Metabolism, published December 30, 2010, 10.1210/jc.2010-2098

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
115
5
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 0 publications
6
115
5
2
Order By: Relevance
“…Therefore, we can hypothesize that the function of thyroid gland was stimulated in the short duration group (group II). This was consistent with Gooley et al [15] who reported that thyroid was relieved from the inhibitory effect of melatonin, as exposure to constant light suppressed its secretion. It might affect thyroid directly or indirectly by affecting hypothalamus-pituitary regulation [12].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we can hypothesize that the function of thyroid gland was stimulated in the short duration group (group II). This was consistent with Gooley et al [15] who reported that thyroid was relieved from the inhibitory effect of melatonin, as exposure to constant light suppressed its secretion. It might affect thyroid directly or indirectly by affecting hypothalamus-pituitary regulation [12].…”
Section: Discussionsupporting
confidence: 92%
“…Concentrations of melatonin ranging from 10 −10 to 10 −7 M increased the expression of SOD1 and catalase, and decreased the levels of ROS generated in HMC‐1 cells. Considering the circulating and testicular melatonin concentrations described in humans by our group and other authors, doses from 1 × 10 −10 to 3 × 10 ‐10 M melatonin can be considered physiological concentrations (Maldonado et al ., ; Zawilska et al ., ; Gooley et al ., ; Morris et al ., ; Rossi et al ., ). As a whole, our findings indicate that melatonin shows anti‐oxidant effects on MCs, thus being in line with numerous reports that point out the ability of physiological concentrations of melatonin to act as a protector against free radical damage (Reiter et al ., , ; Mayo et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…31 More recently, however, it has been shown that, under carefully controlled conditions, retinal exposure to illuminances of as low as 1 lux or less of monochromatic light at wavelength 440 to 460 (blue-appearing light) can significantly lower nocturnal melatonin, 32,33 as can <100 lux of broadspectrum fluorescent light. [34][35][36][37] These same light levels can also elicit significant phase shifts of the circadian clock and directly enhance alertness [37][38][39][40] ; approximately 100 lux exposure will cause about 50% of the maximum response. Such light exposure, when experienced in the evening at home from bedside lamps, TVs, computer screens, tablets, and other devices, causes suppression of melatonin, delays the timing of circadian rhythms, and elevates alertness, all of which make it harder to fall asleep, make it harder to wake up in the morning, and restrict sleep.…”
Section: Impact Of Electric Light At Night On Circadian Rhythmicitymentioning
confidence: 99%
“…Such light exposure, when experienced in the evening at home from bedside lamps, TVs, computer screens, tablets, and other devices, causes suppression of melatonin, delays the timing of circadian rhythms, and elevates alertness, all of which make it harder to fall asleep, make it harder to wake up in the morning, and restrict sleep. 36,41 The physiological mechanism by which light exposure is conveyed to the circadian system is one of the more intriguing topics in modern biology 42 ; a hitherto unknown intrinsically photosensitive retinal ganglion cell (ipRGC) was reported in 2002 in Science. [43][44][45] This novel photoreceptor is anatomically and functionally distinct from the rods and cones used for vision and is a more fundamental aspect of mammalian biology, having evolved before vision.…”
Section: Impact Of Electric Light At Night On Circadian Rhythmicitymentioning
confidence: 99%
See 1 more Smart Citation